Determination of the Optimal Polypropylene Fiber Addition to the Dense Bituminous Mixtures by the Aid of Mechanical and Optical Means - Serkan Tapkin; Şenol Özcan (The Baltic Journal of Road and Bridge Engineering)
Polypropylene fibers are completely native modifiers and they do not have any dependence on abroad in case of technology. When viewed from this point, the modification of bituminous binders with polypropylene fibers is a very important step for our country’s “economical” concerns. In this study, first of all, the physical and chemical effects of polypropylene fibers on bitumen were investigated. Next, the amount of “optimum” polypropylene fibers that has to be added into the mixture was determined. In order to determine it, first, static creep tests and Marshall tests were carried out and then, images of the polypropylene fiber added bituminous binders under fluorescence microscopy were researched. With the application of physical and mechanical tests to the Marshall specimens prepared with the optimum polypropylene amount that was obtained, optimum bitumen content was determined and finally economical analyses were carried out. By carrying out extensive analyses it was seen that the utilisation of polypropylene fibers improves the physical and mechanical properties of the resultant asphalt mixture mainly by enhancing the permanent deformation resistance. On the other hand, polypropylene modification results in 30% economy from bitumen which is a clear indication of the benefit in the mass production of asphalt concrete.